Colaboración científica de la ingeniería química en las universidades españolas - Pulgarín Guerrero, Antonio; LAGAR BARBOSA, Mª Pilar; ESCALONA FERNÁNDEZ, Mª Isabel (Revista General de Información y Documentación, 2010)
A study of the scientific collaboration in chemical engineering produced by the Spanish Universities is presented. A retrospective search in the Web of Science for the period, from 2000 to 2006, it is made. The results provide a high % of authorship multiple (99 %), by assuming the international collaboration of the 36 %. Correlations between the number of articles in each year y its percentage of articles with international collaboration was obtained, and between the number of articles belonging to each category of the JCR and its percentage of articles with international collaboration. However, no correlation in the number of received citations with four or more authors and articles with fewer than four authors was observed, neither there was a significant difference in the received citations average among the groups of articles with international collaboration an articles without international collaboration. The overhanging Universities in what productivity and a bigger collaboration reffers they were the Politécnica of Cataluña, the País Vasco y the Rovira i Virgili.